Effectiveness of Video Tutorial-Based and Conventional Learning Media on Knowledge of Initial Cardiac Assessment in Undergraduate Nursing Students - Ni Luh Putu Manik Mas Puspa Sari; Ni Luh Putu Inca Buntari Agustini; Yustina Ni Putu Yusniawati (Adi Husada Nursing Journal, 2023)
An initial cardiac assessment is an initial assessment that is carried out quickly, precisely, sequentially, simultaneously, and thoroughly on the condition of a patient who shows signs of cardiac arrest. Strong knowledge regarding initial cardiac assessment can help save a patient's life quickly when a case is discovered. The research aims to determine the difference in the effectiveness of video tutorial-based learning media and conventional media on knowledge about initial cardiac assessment among undergraduate nursing students at ITEKES Bali. This research uses a quasi-experimental design with two groups: pre-test and post-test. The sample came from ITEKES Bali level 3 undergraduate nursing students: 34 people in the video tutorial group and 34 people in the conventional group. The sampling technique used was simple random sampling. The initial cardiac assessment knowledge questionnaire, adapted from AHA 2020. Data analysis use Mann-Whitney and Wilcoxon. The results show that video tutorial media and conventional media are effective in increasing student knowledge, with a p-value of 0.001. There is a significant difference between the effectiveness of video tutorial media and conventional media, with a p-value of 0.001. Video tutorial media is more effectively used to increase undergraduate nursing students' knowledge regarding initial cardiac assessment.